2016
DOI: 10.1038/srep29540
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomised, placebo-controlled trial of Ganoderma lucidum for the treatment of cardiovascular risk factors of metabolic syndrome

Abstract: This study aimed to evaluate the efficacy and safety of Ganoderma lucidum for the treatment of hyperglycaemia and other cardiovascular risk components of metabolic syndrome using a prospective, double-blind, randomised, placebo-controlled trial. Eighty-four participants with type 2 diabetes mellitus and metabolic syndrome were randomised to one of three intervention groups: Ganoderma lucidum, Ganoderma lucidum with Cordyceps sinensis, or placebo. The dosage was 3 g/day of Ganoderma lucidum, with or without Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 46 publications
0
38
1
Order By: Relevance
“…It was reported that using G. lucidum (3 g/ d) for 16 weeks had no effect on glycosylated hemoglobin (HbA1c) and fasting plasma glucose (FPG). Further, consumption of G. lucidum was associated with the increased risk of a subset of mild events including headache, fatigue, and gastrointestinal events (Klupp et al, 2016).…”
Section: In Vivo Preclinical Evaluation Of G Lucidummentioning
confidence: 98%
See 2 more Smart Citations
“…It was reported that using G. lucidum (3 g/ d) for 16 weeks had no effect on glycosylated hemoglobin (HbA1c) and fasting plasma glucose (FPG). Further, consumption of G. lucidum was associated with the increased risk of a subset of mild events including headache, fatigue, and gastrointestinal events (Klupp et al, 2016).…”
Section: In Vivo Preclinical Evaluation Of G Lucidummentioning
confidence: 98%
“…Eighty-four volunteers with T2DM and metabolic syndrome were supplemented with extracts of G. lucidum, G. lucidum with Cordyceps sinensis, or placebo in order to manage cardiovascular risk factors. Results from the study evidenced that G. lucidum failed to provide benefit against CVDs in patients with the metabolic syndrome (Klupp et al, 2016). Likewise, the analysis of five trials (398 total volunteers), concluded that G lucidum was not effective in treating elevated BP (Klupp et al, 2015).…”
Section: In Vivo Preclinical Evaluation Of G Lucidummentioning
confidence: 99%
See 1 more Smart Citation
“…Other research showed that purified ganoderma fibrinolytic protease protected mice against thrombotic death or paralysis induced by collagen and epinephrine and also activated the partial thromboplastin time (APTT) and thrombin time (TT) in rat platelets (Kumaran et al, 2011). The polysaccharide of ganoderma was also found to prolong the blood clotting and bleeding time in rats and decrease the thrombosis and fibrinogen level in blood plasma (Klupp et al, 2016). Evidence indicates that ganoderma has potential as an antithrombotic herb because of its antiplatelet activity.…”
Section: Resultsmentioning
confidence: 99%
“…As a medicinal and edible fungus, G. lucidum has been used promote to health, prolong life and prevent diseases for >2,000 years (32). The major phytochemicals in G. lucidum are triterpenoids (33), which have attracted research attention as potential anti-cancer agents (34).…”
Section: Discussionmentioning
confidence: 99%